Story retelling patterns among children with and without hearing loss: effects of repeated practice and parent-child attunement. - Robertson L; Dow GA; Hainzinger SL (Volta Review)
In two analyses, transcripts from 21 children (ages 3-6) reading and retelling stories with a parent over a six-week period were studied. Ten children with moderate-to-profound hearing loss used assistive technology and the Auditory-Verbal approach for language learning; 11 had typical hearing. In Analysis 1, no significant difference between groups was found in the recall of words and phrases from the text, suggesting that children with hearing loss can benefit from shared reading experiences in ways similar to children with typical hearing. Analysis 2 showed that the factors correlating with word recall differed: for children without hearing loss, joint attention was related to remembering; for children with hearing loss, explicit parental scaffolding techniques correlated with memory for the text, suggesting that the involvement of parents of children with hearing loss may need to be more directed to the children's listening needs.